2017
DOI: 10.1002/jsfa.8717
|View full text |Cite
|
Sign up to set email alerts
|

Production of probiotic bovine salami using Lactobacillus plantarum 299v as adjunct

Abstract: Outcomes indicate the workable possibility of using second-quality beef cuts for probiotic salami production. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…19 Similar pH values were reported by Muthukumarasamy and Holley 10 in dry fermented sausages containing 7 log CFU g −1 of L. reuteri, encapsulated by both extrusion and emulsification techniques. On the other hand, Blaiotta et al 20 found higher pH values at the end of 20 days of ripening of bovine salamis produced with L. plantarum 299v as adjunct.…”
Section: Weight Loss Ph and A Wmentioning
confidence: 97%
See 1 more Smart Citation
“…19 Similar pH values were reported by Muthukumarasamy and Holley 10 in dry fermented sausages containing 7 log CFU g −1 of L. reuteri, encapsulated by both extrusion and emulsification techniques. On the other hand, Blaiotta et al 20 found higher pH values at the end of 20 days of ripening of bovine salamis produced with L. plantarum 299v as adjunct.…”
Section: Weight Loss Ph and A Wmentioning
confidence: 97%
“…Microbiological analysis of chorizo sausages was carried out as follows: 10 g of each treatment was taken aseptically and placed in a sterile plastic bag with 90 mL of buffered peptone water (Panreac, Darmstadt, Germany 17 This medium is composed of (in g L −1 ): D-sorbitol (20), agar (15), bacterial peptone (10), beef extract (10), yeast extract (5), sodium acetate (5), potassium phosphate (2), ammonium citrate (2), magnesium sulfate (0.1), manganese sulfate (0.05), bromocresol purple (0.02), and ciprofloxacin (0.0004). Finally, Violet Red Bile Glucose Agar (VRBG) (Panreac, Darmstadt, Germany) with a double layer was used for Enterobacteriaceae (37 ∘ C for 24 h) enumeration.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…In this kind of sausage, the endogenous microbiota can start the meat fermentation process. In addition, LAB are the dominant microorganisms in fermented sausages even if prepared without the incorporation of probiotic or starter culture (Zhao et al, 2011;Triki et al, 2013;Blaiotta et al, 2018). LAB counts may be reduced when the addition of probiotic microorganisms in dry-fermented sausages are as free cells (Ruiz-Moyano et al, 2011).…”
Section: Microbiological Propertiesmentioning
confidence: 99%
“…Beef sausage Lactobacillus plantarum TN8 and Pediococcus acidilactici MA 18/5M [115] Bovine Salami Lactobacillus plantarum 299v [116] Dry fermented sausage Lactobacillus paracasei LPC02 [117] Lactobacillus plantarum L125 [118] Lactobacillus casei ATCC 393 [119] Dry-fermented pork neck and sausage…”
Section: Meat Probiotic Product Probiotic Strains Referencementioning
confidence: 99%